Lateral behaviour of hybrid cold-formed and hot-rolled steel wall systems: Experimental investigation. (August 2018) - Mortazavi, Mina; Sharafi, Pezhman; Ronagh, Hamid; Samali, Bijan; Kildashti, Kamyar
Abstract: The seismic design of light steel frames (LSF) can not only rely on the application of cold-formed steel (CFS). Some mixed systems and integrated solutions such as hybrid systems can offer new possibilities, in particular with regard to applications in mid-rise construction. A hybrid solution is to replace some CFS chord studs with hot-rolled square hollow section SHS, in order to achieve higher capacity. This paper provides the results of experimental studies on the lateral behaviour of a hybrid light-weight steel panel and investigates the implication of any further system improvements for mid-rise construction. Each hybrid wall panel (HWP) consists of a hot-rolled SHS frame, laterally incorporated in a cold-formed panel. The study includes investigating the lateral performance of HWP, while a CFS top chord acting as a load collector, and a hot-rolled steel frame acting as a lateral load resisting system. The behaviour of specimens is investigated under monotonic and cyclic loads, and the step-by-step enhancement is implemented according to the results. The outcomes revealed that although the hysteretic behaviour of the HWP represents pinching effect, mainly due to poor performance of the cold-formed steel collector, by strengthening the top chord design the behaviour is improved. Relying on the cold-formed part to resist the major portion of gravity loads, while the hot-rolled collector transfers the entire lateral load to the hot-rolled frame, results in significantly improved hysteretic behaviour. Highlights: A hybrid solution to replace some CFS chord studs with hot-rolled square hollow section, to achieve higher capacity. Conducting experimental studies on the lateral behaviour of the proposedhybrid light-weight steel panel Investigating the implication of any further system improvements for mid-rise construction Investigating the behaviour under monotonic and cyclic loads, and implementing the step-by-step enhancement